Information Framing And Locus Of Control Effect On Investors’ Interpretation Of Risk - Fitria Husnatarina (Jurnal Akuntansi, 2022)
This study aimed to determine the comparison of IFRS 8 segment reporting with PSAK 5 based on framing information with external risk interpretation. Locus of control, proxied in internal risk preferences analysis by non-professional investors, was also determined. This was an experimental study with a 2x2x2 factorial design between subjects. The subjects comprised 133 novice investors in the Central Kalimantan Investor Community. Furthermore, the data were analyzed using the Analysis of Variance (ANOVA) while the Two Ways Anova Test was used for hypothesis testing. The results showed that, in segment information in IFRS 8 and PSAK 5 stated in positive and negative framing, non-professional investors highly interpret external risk in IFRS 8 cases. Therefore, segment information in IFRS 8 and PSAK 5 expressed positively and negatively is significantly similar to internal risk preferences. However, the hypotheses on locus of control variables were not supported because non-professional investors lack enough experience.